2003
DOI: 10.1046/j.1464-5491.2003.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivational/solution‐focused intervention improves HbA1c in adolescents with Type 1 diabetes: a pilot study

Abstract: These pilot data suggest that a motivational/solution-focused group intervention is promising in improving HbA1c in adolescents and should be investigated further in a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 17 publications
2
91
0
5
Order By: Relevance
“…It extends the evidence and confirms the beneficial impact of psychosocial interventions based on the principles of motivational interviewing that have been previously reported in smaller-scale stud- ies (8,9). Furthermore, this study is one of very few that demonstrate, using a randomized control study design, the potential of a psychosocial intervention to improve glycemic control in children with diabetes over a time period as long as two years (4).…”
Section: Secondary Outcome Measures: Psychosocial Questionnairessupporting
confidence: 86%
See 1 more Smart Citation
“…It extends the evidence and confirms the beneficial impact of psychosocial interventions based on the principles of motivational interviewing that have been previously reported in smaller-scale stud- ies (8,9). Furthermore, this study is one of very few that demonstrate, using a randomized control study design, the potential of a psychosocial intervention to improve glycemic control in children with diabetes over a time period as long as two years (4).…”
Section: Secondary Outcome Measures: Psychosocial Questionnairessupporting
confidence: 86%
“…Motivational interviewing, a counseling approach to facilitate behavioral change (5), has been demonstrated as effective in adults in some health care settings (6,7), and there is preliminary evidence of its effectiveness in improving glycemic control and psychological well-being in teenagers with type 1 diabetes in short-term, uncontrolled trials (8,9). The multicenter randomized controlled trial reported here was developed to replicate and extend the findings of the pilot study (8), employing a fully powered design and an evaluation of longer-term outcomes.…”
mentioning
confidence: 99%
“…However, at 7-12 months the improvement was not maintained. 146 More recently, Channon and colleagues 147 conducted a multicentre RCT which allocated adolescents (14-17 years) to receive either four sessions of MI (n = 38) or support visits (n = 28 …”
Section: Evidence For Motivational Interviewing Based Therapiesmentioning
confidence: 99%
“…diet and exercise) in patients with diabetes [13]. Research has not yet been able to establish full consensus on the effect of MI on clinical [14][15][16][17][18][19] and psychosocial aspects [15,18,[20][21][22] in diabetes. Previous reviews emphasise the need for studies of high methodological quality and adequate power to explore the effect of MI on glycaemic control and wellbeing in patients with diabetes [11,13,23].…”
Section: Introductionmentioning
confidence: 99%